How perception affects house prices: evidence from failed auctions - Cortés, Kristle R; Singh, Mandeep; Solomon, David H; Strahan, Philip E (Review of Finance, 2026)
Abstract In the Australian real estate market, about a third of properties are sold at auction. Properties that fail auctions sell later for a 1.3 percent discount. Consistent with a causal channel, the effect holds with property-level fixed effects and when auction failure is instrumented by adverse weather or seller overvaluation. Prices cluster below round numbers, and the discount fades over time, inconsistent with our effects reflecting unobserved property characteristics. The evidence suggests that there are behavioral factors affecting the valuations of buyers and sellers.